Setting Proteksi Transformator 30 MVA Di Gardu Induk Batu Besar 150/20 KV PT. B’RIGHT PLN Batam Dengan Menggunakan Software ETAP - Reza Al Mattin; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This study aimed to obtain the optimum setting and should be of 30 MVA transformer protection system at Gardu Induk Batu Besar PT B'RIGHT PLN Batam. This study uses the method of observation, which was to determine the object to be studied to make the setting protection 30 MVA transformer in Gardu Induk Batu Besar PT. B'RIGHT PLN Batam. With the data obtained as one line distribution network diagram (SUTM) Gardu Induk Batu Besar PT. B'RIGHT PLN Batam along with data CB, transformers, relays OCR specifications andGFR and tuning the existing condition of the relay, and additional data that support for this thesis as the daily load data and others. From the calculation results with existing data in the field is still in appropriate conditions (the difference is not too much), so that it can be concluded that the overall setting of the OCR and GFR that is in the field is still in goodcondition. OCR for setting relays and GFR in the feeder has approximately the same value where TMS for OCR and GFR respectively 0,15s 0,134s in calculations and in the field toOCR, and 0,104s in calculations and in the field to the GFR 0,1s , But there setting relay is no longer appropriate that the relay setting and GFR OCR on incoming side, where TMS andTMS = 1,5s = 1,2s in other words if there is a short circuit fault then the relay will take a long time to work with the value of t = 5,255s. So setting relays OCR and GFR incoming sidethat is in the field must be set back.Keywords: protection setting, OCR, GFR